2021
DOI: 10.3390/biology10070613
|View full text |Cite
|
Sign up to set email alerts
|

Contiguity and Structural Impacts of a Non-Myosin Protein within the Thick Filament Myosin Layers

Abstract: Myosin dimers arranged in layers and interspersed with non-myosin densities have been described by cryo-EM 3D reconstruction of the thick filament in Lethocerus at 5.5 Å resolution. One of the non-myosin densities, denoted the ‘red density’, is hypothesized to be flightin, an LMM-binding protein essential to the structure and function of Drosophila indirect flight muscle (IFM). Here, we build upon the 3D reconstruction results specific to the red density and its engagement with the myosin coiled-coil rods that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…These findings are consistent with the secondary structure of flightin in Drosophila , which exhibits two helical regions [ 13 ]. Cryo-electron microscopy studies by Menard et al on the thick myofilament of Lethocerus identified a specific red density in the contact area of the thick myofilament skeleton, suggesting the presence of flightin [ 13 , 29 , 30 ]. Our findings suggest that flightin facilitates the contact between multiple myosin dimers, promoting their orderly assembly and stabilizing myosin coils.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the secondary structure of flightin in Drosophila , which exhibits two helical regions [ 13 ]. Cryo-electron microscopy studies by Menard et al on the thick myofilament of Lethocerus identified a specific red density in the contact area of the thick myofilament skeleton, suggesting the presence of flightin [ 13 , 29 , 30 ]. Our findings suggest that flightin facilitates the contact between multiple myosin dimers, promoting their orderly assembly and stabilizing myosin coils.…”
Section: Discussionmentioning
confidence: 99%
“…In Lethocerus, stretch activation has been shown to occur at submaximal calcium concentrations [80]. Many features of the flight muscle lattice have been shown to affect stretch activation including troponin-C isoforms [81], flightin [82,83], the N-terminal extension on the RLC [84], extensions on tropomyosin and troponin [85], and troponin bridges formed from myosin heads [38]. Another stretch activation model proposes that stretch produces enhanced alignment of myosin head origins with actin targets [59].…”
Section: Effect Of Disordered Myosin Heads On Stretch Activationmentioning
confidence: 99%